Effect of post-kidney transplant diabetes mellitus on long-term outcomes in a cohort of pediatric kidney transplant recipients at Hospital Pablo Tobón Uribe from 2005 to 2021 (2024)
ABSTRACT: Background: Post-transplantation diabetes mellitus and carbohydrate intolerance (PTDM/iCHO) are complication following solid organ transplantation, which significantly increases the risk of graft loss and mortality. However, data concerning long-term outcomes in pediatric kidney transplant recipient with PTDM/iCHO is scarce. This study aimed to evaluate the risk of graft loss in pediatric kidney transplant recipients with PTDM or iCHO. Methods: The study cohort included patients aged <18 who underwent a kidney transplant in a tertiary transplant center from 2005 to 2022. The primary outcome was graft survival and secondary outcomes were acute rejection, renal function and mortality. Cumulative incidence of graft loss and acute rejection was estimated, considering death as a competing risk. Fine and Gray's proportional subdistribution hazard model was used to analyze the effect of PTDM/iCHO status on the event. Results: The incidence of PTDM and iCHO was 6.6% and 9.2%. Patients with PTDM/iCHO had a significantly higher cumulative graft loss incidence than those without (34.4% vs. 13.9% at 36 months, p < 0.008). Multivariable analysis revealed a threefold increased risk of graft loss in PTDM/iCHO patients (HRadjusted 3.33, 95% CI 1.19 – 9.30, p = 0.022). PTDM/iCHO was associated with a higher incidence of acute rejection (33.3% vs. 14.5% at 1 year, p = 0.025), particularly T-cell mediated rejection graded higher than 1A. PTDM/iCHO patients also exhibited significantly worse eGFR at all time points compared to non-PTDM/iCHO patients (p = 0.036) Conclusion: PTDM and iCHO patients had a higher risk of graft loss and lower renal function in pediatric kidney transplant recipients. This justifies a close follow-up with these patients also in the pediatric population.